2021
DOI: 10.1109/tvt.2021.3059964
|View full text |Cite
|
Sign up to set email alerts
|

Joint Mobility, Communication and Computation Optimization for UAVs in Air-Ground Cooperative Networks

Abstract: Xuemin (2021) Joint mobility, communication and computation optimization for UAVs in air-ground cooperative networks. IEEE Transactions on Vehicular Technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…The simulation results showed that the proposed method is significantly better than the benchmark methods for the above indicators. Some of the simulation parameters refer to previous works [4] and [13]. The detailed simulation parameters are provided in the next…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The simulation results showed that the proposed method is significantly better than the benchmark methods for the above indicators. Some of the simulation parameters refer to previous works [4] and [13]. The detailed simulation parameters are provided in the next…”
Section: Simulation Results and Discussionmentioning
confidence: 99%
“…It is widely assumed that in different time slots [4], [13], the vehicles movement can be simplified to a uniform acceleration movement. Hence, its motion equation can be expressed as follows:…”
Section: A Mobility Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors in [184] proposed a game theory based solution for offloading the UAVs task while ensuring a tradeoff between the delay, cost, and energy consumption. Recently, Zhou et al [185] proposed a method to jointly optimize the mobility, communication, and computation for a UAV in MEC-assisted air-ground cooperative network to maximize the UAV's energy efficiency. The work in [186] aimed at minimizing the execution time required for UAVs to complete the offloaded tasks by optimizing the UAV's 3D location.…”
Section: B Uav Integration In Mec Networkmentioning
confidence: 99%
“…Mindful of the significant envisioned role of UAV-FANET in future generation mobile networks and beyond, such as seamless and flexible provision of emergency communication coverage and information services [9], we find in the literature, barely few approaches that attempted to efficiently integrate clustering and optimization techniques to improve routing efficiency in FANETs. In one of such approaches, L. Ye et al [3] propose a mechanism able to reduce endto-end delay and increased throughput, but at the expense of high communication overheads.…”
Section: Related Workmentioning
confidence: 99%